DESIGNING SOCIAL SECURITY SYSTEMS: LEARNING FROM AUSTRALIA AND OTHER COUNTRIES. (October 2014) - Podger, Andrew; Stanton, David; Whiteford, Peter; Collins, Paul D.; Podger, Andrew; Dong, Keyong
SUMMARY Social protection systems reflect each country's history, culture and social values, as well as its economic capacity. But, once first established, they can be very hard to redesign as expectations are locked in, and the scale of the systems makes major change a difficult and risky management challenge. This paper describes alternative designs of social security systems and how each addresses the two core objectives of poverty alleviation and income maintenance. Drawing on the 'pillars' typology or framework, the paper describes how different systems are being adjusted to meet changing demographic profiles and economic pressures. It focuses in particular on Australia, which has always emphasised 'foundation pillar' programmes aimed at poverty alleviation and has only recently given emphasis to income maintenance. In doing so, it has chosen a very different approach involving mandated contributions into mostly fully funded schemes where individuals rather than the government and future generations of taxpayers bear most of the risks. Australia has also restructured its schemes for public sector employees. What possible lessons are there for countries at the early stages of design and implementation of a social security system? Copyright © 2014 John Wiley & Sons, Ltd.